Synthesis and Characterization of Coordination Polymers of N-(3-Hydroxy Phenyl) Maleamic acid- Formaldehyde Resins with Some BiposvtiveCations - N.H. Buttrus; W.E. Abbas (College of Education for Pure Sciences, 2005)
The synthesis and characterization of N(3-hydroxy pheriyl) inaleami. acid-formaldehyde resin arc described. The Mn(ll)., Co(U); Ni(II) and Cii(II) chelate of the above resin were prepared. Atomic-absorption results showed the molar ratio of the metal in the complcxe are 1:1 or 2:1, UV-Visible, IR speetra and niagnetie measurements of the complexes suggest tetrahedral and octahedral geometry of the eomplexes. Viscosity measurements in DMSO at 30°C indicate that the complexes are high. iscose.